"And" lesson - bool_two


#1


Hi, all. I know the answer to this one, but would just like an explanation of the maths.

My understanding is that -(-(-(-2))) == -2 is false because -(-(-(-2)) equates to positive 2, which therefore means 2 == -2 is false.

I read it as a negative multiplied by a negative equals a positive, therefore -2 * -2 = 2. But what do the parenthesis and the minus signs all clustered together mean? I've never learned this in math. Is it negative zero multiplied by something, or negative one, etc? I really have no idea!

Thanks



#2

Got there in the end. The equation works on the principles of what results for negative multiplied by positives, vice-versa, or negative multiplied by negative and vice-versa.

Example

Read -(-(-(-2))) as -x(-x(-x(-2

substitute 1 for x

Therefore -1(-1(-1(-2

Step one:

-1 multiply -1 = positive 1

Step two:

positive 1 multiply -1 = -1

Step three:

-1 multiply -2 = positive 2

Therefore 2 == -2 is False.


#3

So did you understand it ? , all i know is parenthesis is first order
Example (2-2)3 first we calculate what inside parenthesis (2-2) = 0 , 03 = 0 so (2-2)*3 =0 not -4
if find you something else let me know ! Thanks


#4

Hey, Azazaz

Yes, I did understand it in the end. I was just thrown by there not being a value in the parenthesis.

Therefore, your explanation of the first order stands true, and validates the equation at bool_two:

As there is no first order equation in the parenthesis, you multiply outside of the first set of brackets and then this result will become the next equation for the remaining bracket:

-(- can be read as -x multiplied by -x, which equals positive x.

This then moves to the next bracket becoming x(- which can be read as positive x multiplied by -x, which equals negative x.

This then moves to -x(-2 which can be read as -x multiplied by -2.

As per the rule 'a negative multiplied by a negative equals a positive', we know the answer of the final equation will be positive, regardless of whatever x may be.

Therefore, our equation is positive x == -2, which is of course false, otherwise it would read -(-(-(-2))) != -2

Not really sure that my explanation makes much sense, but it works in my head :wink: